The Role of Public Health in Infection Control within Healthcare Institutions: Strategies, Challenges, and Impact on Patient and Practitioner Safety - Saud Abdullah Ghazi Alodyani; Walaa Abdulrahman Abualnaja; Hajer Mohammed Algarfan; Fahad Nayif Fahad Aldawood; Ayshah Hamad Hamadan Almtairy; Faisal Rajeh Albaqami; Manal Odah Murdhi Alanazi; Adel Abdullah Ghazi Alotaibi; Abdurahman Abdullah Gazi Alotaibi; Muhammad Abdulaziz AlBarakat; Majed awaidh almotairi; Mohammed Sulaiman Alduraibi; et al. (International Journal of Medical Toxicology and Legal Medicine, 2024)
Public health infection control is very important for healthcare institutions because it focuses on the prevention and management of infectious diseases. Some effective practices include the stringent use of hand hygiene, limited use of personal protective equipment, and sustenance of a sterile environment. Infection rates are picked up through surveillance systems employed by the health organizations to detect and track infection rates in good time for appropriate response to the outbreaks. Poorly solved, these problems seriously impact patient and practitioner protection, as healthcare-associated infections can also lead to increased morbidity, mortality, and costs of healthcare. Success in infection control policies hence goes beyond the level of individual organizations and contributes to improving the health of populations and lessening burdens on healthcare systems. Ongoing education, multidisciplinary collaboration, and evidence based practice are basic contents in the enhancement of infection control efforts and safety culture in healthcare settings.